Investigation of machining performance of the coated carbide cutting tools with acid etching surface pretreatment - Muhammad Fahmi , Jasri (2012)
This research investigated on machining performance of the coated carbide cutting tools with acid etching surface pretreatment. The main objective of this thesis is to investigate the effect of surface pretreatment using acid etching and physical vapour deposition coating (PVD) coating on tungsten carbide (WC) cutting tool. The effect of machining performance on tungsten carbide cutting tool using this pretreatment in term of wear rate also studied. The scope of work include tungsten carbide as cutting tool, acid hydrofluoric, HF for etching, PVD coating process and machining by turning operation. Tungsten carbide cutting tool was subjected to acid etching surface pretreatment for 20 minutes before it was deposited with PVD coating process. Next, the cutting tool was test by turning machine in order to determine the wear resistant and other material characterization also was performed such as surface morphology, hardness Vickers test and surface roughness test. The surface pretreatment with HF acid provide rough surface to tungsten carbide microstructure. Besides, the machining test performance shows the coated tungsten carbide with acid etching surface pretreatment provided longer tool’s life compared to original tungsten carbide and coated tungsten carbide without surface pretreatment cutting tools. In addition, the hardness test indicated that average Vickers hardness of original tungsten carbide specimen was 970.7 HV while coated tungsten carbide with acid etching pretreatment specimen was 1232.33 HV. In surface roughness test, the surface roughness of tungsten carbide increase after subjected to acid etching surface pretreatment but decrease after undergoes PVD coating process. From the result, the acid etching surface pretreatment and PVD coating process affect the mechanical properties of tungsten carbide cutting tool such as microstructure, hardness, surface roughness and wear resistance.